O discurso negacionista contemporâneo no campo político: um estudo de caso - Aguino, Éberton Lopes de (2023)
The global crisis caused by the New Coronavirus (Covid-19) pandemic caused millions of deaths around the world and created a rupture in the functioning of contemporary society, especially connected to the scientific field, political and midiatic. In this moment of crisis, there was an increase in Fake News and social bubbles that proposed the absence of interpretation of speech and led a part of people to believe everything that hears and/or read. In that sense, this work aims has as analysis to understand the speech said denialist by a Brazilian authority during the pandemic in 2020 and how it constituted itself. In this scenario, the role and speech of the President of the Republic in this crisis are extreme important to inform the population. Thus, the present research was developed from a speech uttered in the pronouncement during the Covid-19 pandemic, specifically in early 2020, by former president Jair Messias Bolsonaro, transmitted by an open television and published on websites. In this sense, based on the analysis of this pronouncement, you emphasize the role of former President Bolsonaro's political speech and the prioritization, for example, of the economy to the detriment of science. The work leanes on this speech and argues that Bolsonaro underestimated the gravity of the pandemic and took advantage of this “disinformation” to use it as a political strategy. These issues stand out how the role of this political leader “undermined” science and brought up the denialist discourse, which is why this research is relevant. Furthermore, the work supports is an theoretical analysis by references and discussions made by authors such as Pechêux (2014), Courtine (2014), Maingueneau (2010, 2015) and Eni Orlandi (2005) with the concept of conditions of production (historicity) and with that of subject; Maingueneau (2006, 2015) with the discourse places (paratopia) and Jesus (2006) and Fancelli (2021) with the focus on denialism. As a conclusion of this analysis, we understand that within Bolsonaro's pronouncement, the denialist speech emerges from strategies, that retretat from the scientific speech and also lead us to better understand the notion of denialism and distiguish it from a process closer to the simple act of denying, which implies a speech often without argumentation.